New economic geography in Germany: Testing the Helpman-Hanson model - Steven Brakman; Harry Garretsen; Marc Schramm (Hamburg Institute of International Economics (HWWA), 2002)
In this paper we find evidence that the new economic geography approach is able to describe and explain the spatial characteristics of an economy, in our case the German economy. Using German district data we estimate the structural parameters of a new economic geography model as developed by Helpman (1998) and Hanson (1998) and we find confirmation for a spatial wage structure. The advantage of the Helpman-Hanson model is that it incorporates the fact that agglomeration of economic activity increases the prices of local (non-tradable) services, like housing. This model thereby provides an intuitively appealing spreading force that allows for less extreme agglomeration patterns than predicted by the bulk of new economic geography models. Based on different estimation strategies and taking a number of features of the re-unified German economy into account, we do not only test for the spatial distribution of wages but also for the spatial structure with respect to German unemployment, employment and land prices.
Keywords: R10; R12; R23; 330; economic geography; empirical estimation; Germany; Neue ökonomische Geographie; Raumwirtschaftstheorie; Regionale Konzentration; Interindustrielle Verflechtung; Neue Außenhandelstheorie; Regionale Lohnstruktur; Schätzung; Regionaler Arbeitsmarkt; Bodenpreis; Theorie; Deutschland